Antimicrobial resistance trends of non-fermenter Gram negative bacteria in Saudi Arabia: A six-year national study - Ali Somily; Hanan H. Balkhy; Mushira A.S. Enani; Sahar I. Althawadi; Maha Alawi; Sameera M. Al Johani; Reem AL jindan; Ali AlBarrak; Hisham AlAjlan; Abdulaziz A. AlAgeel; Hala M. Roushdy; Hebah M. Dada; et al. (Elsevier, 2021)
Background: Antimicrobial resistance (AMR) of non-fermenting Gram-negative bacteria (NFGNB) is increasingly recognized as urgent healthcare threat. Trend data on AMR of NFGNB in Saudi Arabia are either old or limited. The objective was to estimate the prevalence and resistance trends of isolated NFGNB in Saudi Arabia. Methods: A retrospective multicenter study involving seven tertiary care hospitals in Saudi Arabia was conducted between 2011 and 2016. Susceptibility testing for non-duplicate isolates was performed according to the Clinical and Laboratory Standards Institute (CLSI) guidelines in College of American Pathologists accredited diagnostic microbiology laboratories in the participating hospitals. Results: Out of 461,274 isolates, 100,132 (21.7%) were NFGNB which represented 30% of gram-negative pathogens. Pseudomonas aeruginosa was the most common (73.6%), followed by Acinetobacter baumannii (21.0%) and Stenotrophomonas maltophilia (5.3%). Resistance trends of P. aeruginosa were increasing for aztreonam (absolute increase during the study was 17.3%), imipenem (12.3%), and meropenem (11.6%). A. baumannii was fully resistant to several beta lactam drugs, and resistance trends were increasing for potential treatments such as tigecycline (25.1%) and tobramycin (15.5%). S. maltophilia was >90% resistant to trimethoprim/ sulfamethoxazole and ciprofloxacin by the end of the study. Conclusion: We are reporting high and/or increasing resistance of NFGNB to common treatment options. The current findings call for urgent actions to combat the increasing resistance of NFGNB. Large scale sharing of AMR data collected at different hospitals with the Saudi AMR committee would be critical to set priorities and monitor progress.